Karma of Cardiovascular Disease Risk Factors for Prevention and Management of Major Cardiovascular Events in the Context of Acute Exacerbations of Chronic Obstructive Pulmonary Disease - Crisan, Liliana; Wong, Nathan; Sin, Don D.; Lee, Hwa Mu (Frontiers in Cardiovascular Medicine, 2019)
Cardiovascular diseases (CVDs) and chronic obstructive pulmonary disease (COPD) are the two leading causes of mortality and morbidity worldwide that coexist frequently. Most recent studies have concluded that patients with CVD or risk factors for CVD are more likely to have major adverse cardiovascular events (MACEs) after an acute exacerbation of COPD, and patients with more severe COPD have higher cardiovascular mortality and morbidity than those with less severe COPD. The risk of MACEs in acute exacerbation of COPD is determined by the complex interactions between genetics, behavioral, metabolic and environmental risk factors. To date, there are no guidelines regarding the prevention, screening, and management of the modifiable risk factors for MACEs in the context of COPD or COPD exacerbations, and there is insufficient CVD risk control in those with COPD. It is not clear whether tight control of the individual (e.g., smoking cessation) or composite CVD risk factors will reduce COPD deaths from cardiac events. A deeper insight of COPD and CVD risk factors may improve the strategies for reduction of MACEs after an acute exacerbation of COPD. Key words: Chronic obstructive pulmonary disease, cardiovascular diseases, major adverse cardiovascular events, risk factors.